Construction Of Telemedicine Implementation License Arrangements Application Based In Indonesia - Shinta Hadiyantina; Dina Imam Supaat; Xaviera Qatrunnada Djana Sudjati; Nur Auliya Rahmatika; Tiara Maharani (Faculty of Law, Universitas Brawijaya, Malang Indonesia, 2025)
Non-Indexed Publication